Brazil, biofuels, and food security in Mozambique - Thali, Kai (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
This chapter, therefore, explores the role of agriculture in Brazilian develop ment assistance programmes and direct investment in Africa, focusing on the potential tensions between biofuel feedstock and food production. After a brief overview of the history of Brazil’s own agricultural development and the country’s relations with Africa, the chapter delves into an examination of Brazilian engagement in the conjoined agricultural and energy sectors of Mozambique, a country that possesses large tracts of arable land and is considered a prime site for biofuel production. The chapter critiques Brazil’s development assistance and investment model and presents ways to improve its effectiveness in order to generate greater benefits for the Mozambican people.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; agriculture / agricultura